2019
DOI: 10.3390/mi10070473
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Integration of Pressure Plus 2-Axis (X/Z) Acceleration Composite TPMS Sensors with a Single-Sided Bulk-Micromachining Technique

Abstract: A novel on-chip integration of pressure plus 2-axis (X/Z) acceleration composite sensors for upgraded production of automobile tire pressure monitoring system (TPMS) is proposed, developed, and characterized. Herein, the X-axis accelerometer is with the cantilever beam-mass structure and is used for automatically identifying and positioning each of the four wheels. The IC-Foundry-Compatible low-cost batch fabrication technique of MIS (i.e., Micro-openings Inter-etch and Sealing) is employed to only fabricate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The sensitivity of the pressure sensor is 0.020 mV/V/kPa, the nonlinearity is 0.4%FS, the sensitivity of the temperature sensor is 0.56 Ω/°C, and the nonlinearity is 0.48%FS. To decrease the chip size and crosstalk between different sensors in integrated chips, Wang et al 127 , 128 developed pressure/acceleration integrated chips, as shown in Fig. 11c, d .…”
Section: “Pressure+ X ” Integrated Chipmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity of the pressure sensor is 0.020 mV/V/kPa, the nonlinearity is 0.4%FS, the sensitivity of the temperature sensor is 0.56 Ω/°C, and the nonlinearity is 0.48%FS. To decrease the chip size and crosstalk between different sensors in integrated chips, Wang et al 127 , 128 developed pressure/acceleration integrated chips, as shown in Fig. 11c, d .…”
Section: “Pressure+ X ” Integrated Chipmentioning
confidence: 99%
“…b Arrangement of piezoresistors for the three-axis accelerometer in (a) 126 . c Sketch of the on-chip integration of the pressure plus two-axis acceleration composite tire pressure monitoring system (TPMS) sensor 127 . d SEM image of the fabricated sensor 127 .…”
Section: “Pressure+ X ” Integrated Chipmentioning
confidence: 99%
See 1 more Smart Citation
“…Dong et al developed integrated acceleration and pressure multifunction sensors with a glass–silicon–glass sandwich structure based on piezoresistive effect, which can be applied to automobile, aerospace, environmental monitoring, and other application fields [ 13 ]. Wang et al proposed composite sensors with pressure and two-axis acceleration that have potential in the mass production of tire pressure monitoring systems (TPMS) with a sensitivity of 0.136 mV/kPa [ 14 ]. With the recent expansion of the automotive electronic products market, and the increasing demand for sensors in the field of intelligent vehicles, sensors applied to the TPMS and intelligent driving field are developing rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Tires, which are in direct contact with the road surface, greatly affect the stability of the vehicle. As a technology that improves vehicle stability and driver convenience, tire-pressure monitoring systems (TPMSs) measure tire pressure and relay that information to the driver [7]. TPMS has been mandatory for automobiles sold in the United States since 2007, and in Korea since 2015 [8,9].…”
Section: Introductionmentioning
confidence: 99%